ANALYSIS OF MODERN RESOURCE-SAVING TECHNOLOGIES MANUFACTURE OF METAL POWDER FOR DIFFERENT PURPOSES - Морозов, Андрей; Омельченко, Ирина (SWorldJournal, 2021)
Every year the consumption of metal products increases and the amount of waste that pollutes the environment are growing. Under such conditions, the problem of forecasting their minimization is relevant. It aims to expand the reuse of resources and second